DIMENSI OLIGOPSONISTIK PASAR DOMESTIK CABAI MERAH - BUDIMAN HUTABARAT; BAMBANG RAHMANTO (SOCA: Jurnal Sosial Ekonomi Pertanian, 2004)
The oligopsonistic market with high potential and persistent growth in domestic demand andsupply has partly led the supply-side government policies in the form of extensification andintensification program of chilli to be ineffective to pursue the objective of improvingfarmer’s welfare. The paper is intended to investigate marketing performance and systemthrough its elements, namely market chain, number and share of maarket agents, agent marketpower. It concludes that farmer receives the least returns relative to others. The wholesaletrader seems to have strong influence in price discovery. Given the circumstances, thegovernment support is called for dissolving the oligopsonistic power of the wholesaler.